2012
DOI: 10.3748/wjg.v18.i47.6885
|View full text |Cite
|
Sign up to set email alerts
|

Macro- or microencapsulation of pig islets to cure type 1 diabetes

Abstract: Although allogeneic islet transplantation can successfully cure type 1 diabetes, it has limited applicability. For example, organs are in short supply; several human pancreas donors are often needed to treat one diabetic recipient; the intrahepatic site may not be the most appropriate site for islet implantation; and immunosuppressive regimens, which are associated with side effects, are often required to prolong survival of the islet graft. An alternative source of insulin-producing cells would therefore be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 74 publications
0
52
0
1
Order By: Relevance
“…11 Several preclinical trials using macroor microencapsulation of porcine islets demonstrated efficacy for several years without the need for immunosuppressants. 12 …”
Section: Isletsmentioning
confidence: 99%
“…11 Several preclinical trials using macroor microencapsulation of porcine islets demonstrated efficacy for several years without the need for immunosuppressants. 12 …”
Section: Isletsmentioning
confidence: 99%
“…Numerous studies on islet microencapsulation have been published and reviewed on various rodent diabetes models [35,36]. However, this approach has shown limitations in achieving significance within large animals and human clinical trials [37][38][39][40][41][42][43]. The standard islet encapsulating alginate microcapsules are produced by dropwise addition of sodium alginate, mixed with islets, into a bath of CaCl2 or BaCl2, which rapidly crosslinks to form a hydrogel capsule containing the islet.…”
Section: Microencapsulationmentioning
confidence: 99%
“…Количество доклинических испытаний со свиными островками на людях крайне ограничено, хотя свиные островки сохранялись и функционировали в течение до 6 ме-сяцев у нечеловеческих приматов с применением иммуносупрессии [16]. Несколько доклинических испытаний с использованием макро-или микроин-капсуляции свиных островков продемонстрирова-ли, что их имплантация давала позитивный эффект в течение нескольких лет без использования имму-носупрессии [17]. Тем не менее сохраняется мне-ние о том, что трансплантация островков свиньи остается несовершенным методом лечения в связи с ограниченной долгосрочной жизнеспособностью in vivo и постоянной потребностью в применении иммуносупрессивных препаратов [18].…”
Section: островки пжunclassified